Perbandingan Tingkat Kepercayaan Diri Ditinjau Dari Jenis Kelamin Pada Siswa SMA Negeri 1 Cerme - Rizka Hadi Trimayati; Ima Fitri Sholichah; Setyani Alfinuha (Psikosains: Jurnal Penelitian dan Pemikiran Psikologi, 2023)
One of the problems that occurs in high school students today is lack of confidence in their abilities to continue their studies after graduating from high school. The purpose of this study was to find out whether there are differences in the level of self-confidence between male and female students in class XII at SMA Negeri 1 Cerme. The subject of this study was class XII students at SMA Negeri 1 Cerme. A total of 132 students were divided into 66 male students and 66 female students. The data collection technique used self-confidence questionnaire. The hypothesis testing was carried out by analyzing the median test analysis. The results of testing the hypothesis obtained Sig. (2-tailed) 0.001 <0.05, so the hypothesis in this study can be accepted, or it can be said that there is a significant difference in the difference in the level of self-confidence between male and female students.